Rascal - North, Sterling, 1906-1974.; Schoenherr, John (New York : Scholastic, 1991)
The author recalls his carefree life in a small midwestern town at the close of World War I, and his adventures with his pet raccoon, Rascal.
"First Scholastic printing, May 1991" -- T.p. verso.
RL4
Ages 8-12
1140
Accelerated Reader AR
Newbery Honor, 1964
Keywords: North, Sterling, -- 1906-1974 -- Childhood and youth; Authors, American -- 20th century -- Biography; Rascal (Raccoon); Raccoon -- Wisconsin -- Biography; Country life -- Wisconsin; Raccoons; Raccoon; Country life -- Wisconsin